DEVELOPING INTERCULTURAL COMPETENCE THROUGH LITERATURE - Nugrahenny Zacharias (Soegijapranata Catholic University, 2005)
In the area of language teaching, it is widely known that there is a de-facto segregation between literature and culture. Both literature and culture are taught separately. Rarely do the two meet in one classroom regardless the strong ties between them. It is without doubt that literature is the media where elements of culture blend and interact. Literature is the media in which people reflect and challenge either their own culture or others. Unfortunately, literature rarely has a role as far as culture teaching and learning are concerned. This brings to the central thrust of this paper. In this paper, I would argue that literature is the best way to facilitate culture learning. It suggests how literary texts, if chosen selectively, would pave the way to cultural awareness and reflection. In addition, not only will students learn about culture but they will also experience personal enjoyment and emotional gain throughout the process. It will end with samples of activities where literature is used.